Tech-Transformed Teaching: The Influence of AI Writing Tools and Blended Learning on Rural Education - Kamarullah, Kamarullah; Fadhilah, Muhammad Arif; Syahmidi, Humaira; Maulya, Ranti; Sarinauli, Barep (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
This study investigates the impact of AI Writing Tools (AIWT) and Blended Learning (BL) on the writing skills of students in rural educational settings and explores the adaptations required by teachers to effectively integrate these technologies. Using a mixed-methods approach, the research assesses how AIWT and BL enhance English writing proficiency among high school students and identifies the infrastructural and pedagogical challenges faced by English teachers. The findings reveal that AIWT and BL significantly improve student engagement and writing quality by providing personalized feedback and fostering more interactive learning environments. The students showed marked improvements in grammar, vocabulary, and overall coherence in their writing. However, the research also highlights challenges such as variable technological proficiency among teachers and infrastructural limitations in rural schools. The study emphasizes the necessity for targeted professional development and infrastructure enhancements to fully leverage the benefits of AIWT and BL in rural educational settings. It suggests that effective integration of technology requires not only technological tools but also comprehensive support systems to assist teachers in overcoming adaptation challenges. These findings offer critical insights for policymakers and educational leaders to develop strategies that support the sustainable implementation of educational technologies, thereby optimizing learning outcomes in underserved regions.